THE KEY FACTORS OF ATHLETES’ FUNCTIONAL FITNESS - Kolumbet, A. N.; Paryshkura, Yu. V.; Kostiuchenko, M. A. (Rehabilitation and Recreation, 2025)
Purpose is to study the most generalized properties (factors) of functional systems that make up functionalfitness structure and to analyze the possibilities of diagnosing the functional fitness of skilled athletes (cyclistsand rowers) based on complex research of the body oxygen transport system. Material and methods. The results of 264 complex physiological individual examinations conducted over a number of years using a holisticmethodological approach (and specially adapted methods) were analyzed. One of the main tasks of our study was the development of methods for quantitative assessment of functional fitness factors, as well as some other theoretical and factual grounds for making a diagnostic model of functional fitness. A complex methodology for functional fitness level determination was used. It included registration of the main gas exchange parameters, external respiration, blood, and cardiovascular system at different loads. Results. The main factors of athletes’ functional fitness are power, mobility, stability, economy, and functional potential realization. The power ofsystems determines the limit of functional manifestations in sports activity conditions. The mobility of systems determines the development speed of functional and metabolic responses at changes in work pace and intensity.The stability of systems determines the ability to keep high levels of energy and functional reactions. The economy of systems determines the functional and metabolic “cost” of the levels of work, gas transport and oxygen consumption, general economy of energy conversion. The degree of realization of the body system functional potential depends on the individual peculiarities of the neurovegetative status. Conclusions. The development of methods for analysis and assessment of the properties of function regulation that underlie the work capacityprovision in cyclic sports events, as well as some other parameters that reflect the body functional potential, is of great importance for functional fitness diagnostics. Determination of the properties of the main functional systems regulation not only helps to explain the mechanisms of formation and manifestation of functional fitness structure factors and to obtain additional information about them but also can serve as a very efficient independent criterion for the body functional potential analysis.